Transformation of Aqidah Akhlak Learning through Game-Based Learning Using Zeep Quiz at State Senior High School 1 Imogiri - Komalasari, Komalasari; Putra, Lovandri Dwanda; Aulia, Fajrina; Purnama, Delvia Dwi; Shofia, Zakiatus; Saputri, Oke (Jurnal Ar Ro'is Mandalika (Armada), 2026)
With technological advancements, more schools are starting to use technology, particularly in Islamic Religious Education (PAI) learning. Teachers play an important role in utilizing technology, one of which is through game based learning methods (GBL). This method provides an enjoyable and varied learning experience with game elements such as scores, challenges, and rewards. This study explores the use of GBL in PAI at SMA Negeri 1 Imogiri using the Zep Quiz online platform. The study employs a qualitative approach with direct observation at the school as well as classroom learning practice with students. In addition, this research also uses a literature review from various relevant journals as a theoretical basis. The results of the study indicate that the use of the Zep Quiz web, which allows students to access materials and quizzes interactively, is effective in increasing learning motivation and student achievement. Through observation and classroom practice at SMA Negeri 1 Imogiri, it was found that this website also provides an evaluation feature at the end of learning that helps students understand their level of mastery of the material. Thus, the implementation of Game Based Learning (GBL) through Zep Quiz has been proven capable of creating a learning atmosphere that is more effective, engaging, and relevant to the needs of PAI learning in the digital era.